Cloning of a trehalose-6-phosphate synthase gene from Exopalaemon carinicauda and its expression response to bacteria challenge. Issue 93 (October 2019) - Zhang, Jiquan; Liu, Yujie; Zhou, Yongzhao; Wang, Wenzheng; Su, Naike; Sun, Yuying
Abstract: Trehalose, a nonreducing disaccharide, is present in a wide variety of organisms and plays a key role in many organisms under different stress conditions. In the study, the full-length cDNA sequence encoding trehalose-6-phosphate synthase (EcTPS) was obtained from Exopalaemon carinicauda . The complete nucleotide sequence of EcTPS contained a 2532 bp open reading frame (ORF) encoding a putative protein of 843 amino acids. The domain architecture of the deduced EcTPS contained a glycol_transf_20 domain and a trehalose_PPase domain. EcTPS mRNA was predominantly expressed in the hepatopancreas. The expression of EcTPS in the prawns challenged with Vibrio parahaemolyticus and Aeromonas hydrophila changed in a time-dependent manner. The function of EcTPS was also studied by double-strand RNA interference. The results showed that the knock-down of EcTPS increased the mortality of the Vibrio -challenged group and Aeromonas -challenged group compared with the control group. The present study provides some new insight into the immune function of the trehalose-6-phosphate synthase in prawns. Highlights: EcTPS was identified in E. carinicauda. EcTPS was predominantly expressed in the hepatopancreas of E. carinicauda. EcTPS was upregulated after the challenge with V. parahaemolyticus or A. hydrophila. Knock-down of EcTPS increased the mortality of bacteria-challenged prawns.